PELAKSANAAN PUNGUTAN PAJAK BUMI DAN BANGUNAN BERDASARKAN UNDANG-UNDANG NOMOR 28 TAHUN 2009 TENTANG PAJAK DAN RETRIBUSI DAERAH ( STUDI DI KABUPATEN INDARAGIRI HILIR) - Muhsin (Fakultas Hukum Universitas Islam Indragiri, 2017)
Tax is the contribution of the people to the State treasury under the Act, by not receiving lead services (kontraprestasi) that can be directly demonstrated and used to pay public expenditure. All types of levies and taxes must be based on legislation